The Effects of Reading Strategy Awareness on L2 Comprehension Performance among the Rungus in North Borneo - Nalmon, Goyi; Rohaidah, Kamaruddin; Zuraini, Seruji; Noor Aina, Dani (Australian International Academic Centre PTY.LTD., 2021)
The Rungus are the indigenous people in Sabah, Malaysia. Malay as a second language and the primary instruction in schools seems inevitable. The study aims to determine the effects of reading strategies in the L2 reading comprehension tests on textual content and vocabulary. Participants consisted of twenty-six Form Four Rungus tribe pupils from Kudat Sikuati II Government Secondary School. The study used an ex-post facto research design. The researchers employed cognitive and metacognitive strategy questionnaires and two reading comprehension tests on L2 textual content and vocabulary. The researchers applied Cronbach alpha reliability statistics, paired sample test, and regression analysis. The study indicates that the L2 reading comprehension test on textual content and cognitive strategy were linearly related. Also, the factors related to L2 vocabulary in the reading comprehension test and metacognitive strategy are statistically significant. There is a very substantial relationship between past knowledge and reading comprehension among the participants. This study found that the use of cognitive strategies facilitates L2 reading comprehension with first language translation. The participants use translation strategies at a high level. However, they often use the metacognitive strategy more than the cognitive strategy. There is a significant positive relationship between metacognitive awareness and high-skilled readers’ performance. Low-level skilled readers choose the cognitive strategy. Meanwhile, the regression analysis between the L2 reading comprehension test on textual content and cognitive strategy revealed a positive association (β=.435) that is statistically significant (p<.05). The regression analysis between the L2 reading comprehension test on vocabulary and metacognitive strategy indicated a positive association (β=.440) and statistically significant (p<.05). Reading strategies facilitate students to understand the text, thereby improving their reading comprehension tasks. In addition to demonstrating positive implications on teaching students to read a second language, the findings are essential for teaching Malay language vocabulary. The schema theory employed in the study implicates that reading comprehension performance is generated from the interaction between top-down strategy (metacognitive) and bottom-up strategy (cognitive). A large-scale study could potentially reveal the use of translation strategy as a strategic trait associated with high-achievement readers or is, in fact, a bilingual additive.